Oligarchic forests of Oecopetalum mexicanum enriched with native species of Sierra de Misantla, Veracruz, Mexico - Covarrubias, Melissa; López-Acosta, Juan Carlos; Lascurain Rangel, Maite; Rebolledo, Virginia; Pedraza, Rosa Amelia; Avendaño Reyes, Sergio (Instituto de Ecología, A.C., 2018)
The practice of enrichment of managed forests implies the insertion of species with cultural, economic and ecological value. It generally takes place in sites with some degree of anthropic impact, and also applies in sites known as oligarchic forests. They are historically modified and man-managed systems to favor a single species. Examples are the cachichinales woodlands typical of the Sierra de Misantla region, Veracruz, dominated by Oecopetalum mexicanum, a tree of edible seeds. In this study, two planting techniques were tested: translocation and nursery transplantation of three tree species highly valued in the region: Ocotea puberula, Beilschmiedia anay and Pseudolmedia glabrata. We used a paired model (Anova) to evaluate its physiological state, growth and survival. All three species showed marked stress in the early stages of their establishment; a survival rate greater than 50% was recorded after one year, regardless the technique used for either specie. Growth-wise, O. puberula was the most successful; although we found overall high survivals rates in all three species, which lead us to conclude it is feasible to introduce them into cachichinales.